Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Inflammation-targeted bioactive SiMo glass-ceramic nanozymes for adaptive and sequential infection-impaired wound repair through precise immunoregulation and antiinfection - Jing Tian; Yanzi Zhao; Yanping Zuo; Xiaochen Su; Long Zhang; Weipeng Qiang; Zuhao Zhang; Minhui Ai; Houjin Zhuang; Qian Huang; Meng Luo; Bo Lei (Chemical Engineering Journal, 2026)

Single-nucleus RNA sequencing reveals a spatiotemporal pattern of H2S signaling in Chinese cabbage - Jiao Zhang; Yang Chen; Bo Liu; Yuwei Qin; Yue Luan; He Yin; Wenqi Liu; Limei Chen; Jixian Zhai; Yanxi Pei; Yanping Long; Zhuping Jin (Science China Life Sciences, 2026)

Explainable daily warning of algal concentration exceedance from SHAP-guided temperature and light thresholds - Dawei Xu; Yanping Hu; Shouye Yang; Lu Wang; Long Wang (Journal of Environmental Chemical Engineering, 2026)

Genome characterization of a novel chrysovirus infecting Aspergillus Niger - Li Wang; Futao Huang; Jia Mi; Changfeng Long; Yelin Xu; Xiaolan Qi; Yanping Jiang; Tom Hsiang; Yinhui Jiang (Archives of Virology, 2026)

Bone marrow mesenchymal stem cells promote the recovery of stroke in rats with type 2 diabetes mellitus by inhibiting the activation of TLR4/NF-κB signaling pathway - Fan Peng; Yanping Long; Taolin Zheng; Minghui Leng; Hui Deng (Molecular and Cellular Biochemistry, 2025)

The impact of season, temperature, and direct normal irradiance on IVF pregnancy outcomes: a retrospective cohort study - Chao Wang; Jiehua Chen; Zhong Lin; Li Shi; Qiuyan Ruan; Jiamin Long; Yanping Lao; Xiangli Niu (International Journal of Biometeorology, 2025)
Objective . This study assessed associations between season, temperature, direct normal irradiance (DNI), and clinical pregnancy outcomes in first fresh in vitro fertilization (IVF) cycle. Methods . We conducted a retrospective cohort study (June 2021-October 2023) of 1179 patients undergoing fresh IVF cycles. Inclusion criteria required age ≤ 45 years, first-time fresh embryo transfer cycles (long/antagonist protocol), excluding preimplantation genetic testing, frozen cycles, or incomplete data. Temperature and DNI were recorded from gonadotropin (Gn) initiation to oocyte retrieval. Binary logistic regression assessed seasonal impacts on clinical pregnancy, while restricted cubic splines (RCS) independently modeled temperature/DNI effects. Results . Compared to winter, clinical pregnancy likelihood was 1.74-fold higher in spring (95% CI:1.11–2.71, P = 0.015) and 1.53-fold in summer (95% CI:1.02–2.30, P = 0.042). Stratified analysis revealed a 2.02-fold increased likelihood in summer cycles using the long protocol (95% CI:1.07–3.82, P = 0.031), whereas no seasonal variation was observed in antagonist protocol. RCS regression analysis indicated a nonlinear relationship between temperature and clinical pregnancy outcomes, which was confirmed in the long protocol group. No significant correlations were observed with DNI or in patients treated with the antagonist protocol. Conclusions . Season and ambient temperature significantly impact IVF clinical pregnancy, especially in the long protocol, with the highest increase in pregnancy rates observed in summer, as well as within the 26.13℃ to 29.68℃ temperature range. No significant effects were observed with DNI or the antagonist protocol. These findings suggest that summer treatment may optimize IVF outcomes, but future studies should prioritize multi-center prospective designs with continuous temperature monitoring to define precise optimal ranges.

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Fluorinated Zn-porphyrin covalent organic frameworks with optimized hydrophobic/hydrophilic balance towards stable Zn anodes - Xia Li; Yanping Chu; Shouliang Lu; Liangdan Chen; Long Su; Fei Lu; Zhen Chen; Xinpei Gao (Chemical Engineering Journal, 2025)

A portable microfluidic platform for ultra-sensitive detection of ovarian cancer biomarkers via cascade signal amplification - Yuzhen Wang; Wenxiu Long; Yanping Wang; Yuanyue Han; Fei Zeng; Jingjing Li; Bangshun He; Yujun Song; Yanfeng Gao (Chemical Engineering Journal, 2025)

Recovery of Coilia nasus resources after implementation of the 10-year fishing ban in the Yangtze River: implied from the Yangtze River Estuary and its adjacent sea areas - Shuyan Wang; Ying Xiong; Hushun Zhang; Dade Song; Yanping Wang; Hui Ge; Chengbin Zhang; Long Liang; Xiaming Zhong (Frontiers in Marine Science, 2024)
Introduction The implementation of the 10-year fishing ban in the Yangtze River has provided a crucial opportunity for the recovery of rare and endangered diadromous species, such as Coilia nasus . Methods In this study, we utilized electronic length–frequency analysis (ELEFAN) and length-based Bayesian biomass estimation (LBB) method to fit the body length data of C. nasus from the Yangtze River Estuary and its adjacent sea areas before and after the fishing ban (2019-2023), and the resource changes of C. nasus population were evaluated. Additionally, combined the catch production monitoring data from 2020 to 2022, we comprehensively analyzed the impact of the Yangtze River fishing ban on the recovery of C. nasus resources. Results The results showed that: (1) The proportion of quantity, weight and occurrence frequency of C. nasus in catches showed a significant increasing trend year by year. (2) 4,994 C. nasus were caught from 2021–2023, with body lengths ranging from 13–410 mm. In 2023, the average body length and weight of C. nasus had increased by 39.93% and 133.89%, respectively, from those in 2021. (3) ELEFAN estimated that the growth parameters after fishing ban, including asymptotic length, growth coefficient, and the theoretical age at length zero, were determined to be 42.92 cm, 0.43 year -1 , and -0.31 year, respectively. The total mortality rate, fishing mortality rate, and exploitation rate were determined to be 1.47 year -1 , 0.79 year -1 , and 0.54, respectively. (4) LBB estimated that the relative fishing mortality of C. nasus before the fishing ban increased from 1.22 in 2019 to 2.65 in 2020, while the relative biomass decreased from 0.34 to 0.22. After the fishing ban, the relative fishing mortality decreased from 0.85 in 2021 to 0.06 in 2023, and the relative biomass increased from 0.26 in 2021 to 0.90 in 2023, with a significant increase in 2022, indicating a clear recovery trend in C. nasus resources. Discussion By quantifying the resource characteristics of C. nasus before and after the 10-year fishing ban on the Yangtze River, this research revealed the impact of the ban and provided a reference for future systematic evaluations of the C. nasus population.

Hexagonal liquid crystals as emerging quasi solid-state electrolytes for aqueous lithium-ion batteries - Weirong Ren; Zhaowei Hou; Long Su; Xinpei Gao; Yanping Chu; Liqiang Zheng; Fei Lu (Chemical Engineering Journal, 2024)

Activation of peroxydisulfate by zero valent iron-carbon composites prepared by carbothermal reduction: Enhanced non-radical and radical synergies - Chengjie Xue; Yanping Luo; Yifu Peng; Long Zhou; Jiaru Zheng; Kai Zhang; Zhanqiang Fang (Environmental Pollution, 2024)

Baseline sensitivity and fungicidal action of iminoctadine tris (albesilate) against Geotrichum citri-aurantii - Kunyu Zhang; Yanping Fu; Chaoan Long; Fuxing Zhu (European Journal of Plant Pathology, 2024)

Effects of saline water with different concentrations of calcium and magnesium ions on emitter clogging in drip irrigation integrated water–fertilizer system - Long Zhou; Chenchen Wei; Peiling Yang; Yunkai Li; Lili Zhangzhong; Yanping Su; Xin Wang; Xin He (Irrigation and Drainage, 2024)
The application of saline water in drip irrigation is severely constrained due to its high salt content, which causes precipitation and emitter clogging. Therefore, the effects of calcium and magnesium ions at 100, 150 and 200 mg/L in saline water coupled with humic acid nitrogen fertilizer on emitter clogging were studied. Compared with ground saline water, all treatments significantly increased the emitter clogging risk. In the calcium and magnesium ion treatment groups, clogging fouling increased by 23.94–58.35 and 14.55–51.21 mg/cm 2 , the discharge variation ratio (Dra) decreased by 22%–59% and 14%–49%, and the Christiansen coefficient of uniformity (CU) decreased by 29%–79% and 15%–74%, respectively. Higher ion concentrations caused more clogging. Saline water with a high calcium content caused more clogging. Under similar concentration conditions, the Dra and CU in high magnesium saline water were 9%–32% and 8%–51% higher, respectively. In addition, the increase in magnesium ion concentration changed the crystal form of carbonate, slowed the formation rate of precipitated dirt and significantly reduced the carbonate content by 19%–40%. Our results provide support for the popularization of saline water drip irrigation systems.

Iminoctadine tris (albesilate) resistance in Geotrichum citri-aurantii and its management - Kunyu Zhang; Yanping Fu; Chaoan Long; Fuxing Zhu (Crop Protection, 2024)

Novel aloe emodin–hydroxyethyl piperazine hybrid dihydrochloride induces oral cancer CAL-27 cells apoptosis through ROS production, DNA damage and mitochondrial pathways - Xing Long; Peilin Yang; Lin Chen; Wen Zhong; Shaofeng Chen; Yanping Li; Shijie Lin; Wei Tian (Medicinal Chemistry Research, 2023)

In vitro and in vivo synergistic effects of hydroxychloroquine and itraconazole on Cryptococcus neoformans - Xue Wang; Xuemei Long; Songgan Jia; Jiali Zhu; Zhan Zhou; Sarah Ahmed; Yinhui Jiang; Yanping Jiang (Folia Microbiologica, 2023)

Insight into structural characteristics of theabrownin from Pingwu Fuzhuan brick tea and its hypolipidemic activity based on the in vivo zebrafish and in vitro lipid digestion and absorption models - Yue Xiao; Yanni Huang; Feiwu Long; Dongmei Yang; Yan Huang; Yuanyuan Han; Yanping Wu; Kai Zhong; Qian Bu; Hong Gao; Yina Huang (Food Chemistry, 2023)

Host adaptation of codon usage in SARS-CoV-2 from mammals indicates potential natural selection and viral fitness - Yanan Fu; Yanping Huang; Jingjing Rao; Feng Zeng; Ruiping Yang; Huabing Tan; Zhixin Liu; Weixing Du; Long Liu (Archives of Virology, 2022)

Effects of Symbiodiniaceae Phylotypes in Clades A–E on Progeny Performance of Two Giant Clams (Tridacna squamosa and T. crocea) During Early History Life Stages in the South China Sea - Chao Long; Yuehuan Zhang; Yunqing Li; Jun Li; Zihua Zhou; Yanping Qin; Xingyou Li; Haitao Ma; Jinkuan Wei; Yinyin Zhou; Zohaib Noor; Lijuan Long; et al. (Frontiers in Marine Science, 2021)
Unlike most bivalves, giant clams (tridacnids) harbor symbiotic microalgae (zooxanthellae) in their other fleshy bodies. The effects of mixed populations of zooxanthellae on larval metamorphosis has been reported in several papers, but there have been very few studies on the effects of single zooxanthella species on the establishment of symbiosis in giant clams. In this study, we obtained five pure zooxanthella species (clades A3, B1, C1, D1, E1) from antler coral by molecular identification, and analyzed their effects on the larval metamorphosis and progeny performance of two giant clams, Tridacna squamosa and T. crocea , in the South China Sea. Clam larvae with all five zooxanthella species underwent larval settlement and metamorphosis, and formed the zooxanthellal tubular system. There was some variation in metamorphic rate and time to metamorphosis between clams with different zooxanthella species, but no significant differences in size at metamorphosis. After metamorphosis, larvae with all zooxanthella types continued to develop normally. Mantle color was consistent within clam species and zooxanthella species had no effect on mantle color. However, clam progeny with clade E1 zooxanthellae were smaller than progeny with the other four zooxanthella clades (A3, B1, C1, and D1). Survival rate was over 90% for all progeny and there were no significant differences in survival between progeny with Symbiodinium clades A–E during the entire culture process. Two-way ANOVA analysis revealed that giant clam species was the main factor influencing progeny growth, with some variation in growth attributable to zooxanthella type. Our results provide new information on both the symbiotic relationship between giant clams and zooxanthellae and the mantle coloration of giant clams, and will be useful in giant clam seed production and aquaculture.

Impact of Biological Treatment Techniques on Perfluoroalkyl Acids Emissions in Municipal Sewage - Xinxuan Wang; Ruobing Zhang; Hong Zhang; Long He; Jincan Shen; Zhifang Chai; Bo Yang; Yanping Wang (Water, Air, & Soil Pollution, 2016)

Genomic comparison of Yersinia pestis and Yersinia pseudotuberculosis by combination of suppression subtractive hybridization and DNA microarray - Xiaoyi Wang; Dongsheng Zhou; Long Qin; Erhei Dai; Jianguo Zhang; Yanping Han; Zhaobiao Guo; Yajun Song; Zongmin Du; Jin Wang; Jun Wang; Ruifu Yang (Archives of Microbiology, 2006)